Video course in behavioural observation - Neads, Carl; The University of Liverpool. Department of Psychology (Leesburg, VA : The University of Liverpool, 1996)
This course consist of 4 volumes is design to teach students the fundamentals of behavioural observation. The primary aim is to stimulate students to think about the purposes and the methodology of behavioural observation, to try it out for themselves, and to appreciate, critically, the usefulness of explicit categorisation
vol. 1. Focussing in (48 min.) - vol. 2. Keys to success (49 min.) - vol. 3. Representative sample (31 min.) - vol. 4. Observing ourselves (29 min.)
Title from title screen
Editor, Kevin Jones, Dave Johnson ; graphic design, Susan Wilson ; cameras, Kevin Jones...[et al.]
Narrated by David Dickins
Keywords: Observation (Psychology); Behavioral assessment; Participant observation